T Follicular Helper Cells in Autoimmune Disorders - Gensous, Noémie; Charrier, Manon; Duluc, Dorothée; Contin-Bordes, Cécile; Truchetet, Marie-Elise; Lazaro, Estibaliz; Duffau, Pierre; Blanco, Patrick; Richez, Christophe (Frontiers in Immunology, 2018)
T follicular helper (Tfh) cells are a distinct subset of CD4+ T lymphocytes, specialized in B cell help and in regulation of antibody responses. They are required for the generation of germinal center reactions, where selection of high affinity antibody-producing B cells and development of memory B cells occur. Owing to the fundamental role of Tfh cells in adaptive immunity, the stringent control of their production and function is critically important, both for the induction of an optimal humoral response against thymus-dependent antigens but also for the prevention of self-reactivity. Indeed, deregulation of Tfh activities can contribute to a pathogenic autoantibody production and can play an important role in the promotion of autoimmune diseases. In the present review, we briefly introduce the molecular factors involved in Tfh cell formation in the context of a normal immune response, as well as markers associated with their identification (transcription factor, surface marker expression and cytokine production). We then consider in detail the role of Tfh cells in the pathogenesis of a broad range of autoimmune diseases, with a special focus on systemic lupus erythematosus and rheumatoid arthritis, as well as on the other autoimmune / inflammatory disorders. We summarize the observed alterations in Tfh numbers, activation state and circulating subset distribution during autoimmune and some other inflammatory disorders. In addition, central role of interleukine-21, major cytokine produced by Tfh cells, is discussed, as well as the involvement of follicular regulatory T (Tfr) cells, which share characteristics with both Tfh and regulatory T cells.